How much does it cost? The LIFE Project - Costing Models for Digital Curation and Preservation - Davies, Richard; Ayris, Paul; McLeod, Rory; Shenton, Helen; Wheatley, Paul (LIBER Quarterly: The Journal of the Association of European Research Libraries, 2007)
Digital preservation is concerned with the long-term safekeeping of electronic resources. How can we be confident of their permanence, if we do not know the cost of preservation? The LIFE (Lifecycle Information for E-Literature) Project has made a major step forward in understanding the long-term costs in this complex area. The LIFE Project has developed a methodology to model the digital lifecycle and to calculate the costs of preserving digital information for the next 5, 10 or 100 years. National and higher education (HE) libraries can now apply this process and plan effectively for the preservation of their digital collections. Based on previous work undertaken on the lifecycles of paper-based materials, the LIFE Project created a lifecycle model and applied it to real-life digital collections across a diverse subject range. Three case studies examined the everyday operations, processes and costs involved in their respective activities. The results were then used to calculate the direct costs for each element of the digital lifecycle. The Project has made major advances in costing preservation activities, as well as making detailed costs of real digital preservation activities available. The second phase of LIFE (LIFE2), which recently started, aims to refine the lifecycle methodology and to add a greater range and breadth to the project with additional exemplar case studies.